GANGGUAN KESEHATAN MASYARAKAT YANG BERMUKIM DI SEKITAR TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH PIYUNGAN - Rendi Ariyanto Sinanto; Astry Axmalia; Widodo Hariyono; Surahma Asti Mulasari (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
Health risks can occur if people live close to the landfill. This study aims to determine the health problems of the people who live around the Piyungan landfill. Using a purposive sampling technique, this study involved six participants who lived around the Piyungan garbage dump. The instrument used was a human instrument with interview guidelines, as well as observation and content analysis. The results showed that all participants worked as scavengers and experienced symptoms of health problems. Health complaints felt by all participants were headache, cough, runny nose and shortness of breath. While 83% felt a sore throat, 66% felt itchy skin, and 50% complained of nausea. Continuous contact with garbage gives a high risk of experiencing health problems. It is hoped that people who work as scavengers at the Piyungan landfill can increase efforts to reduce health impacts by carrying out clean and healthy living behaviours such as washing hands before and after eating, changing work clothes every day, and using personal protective equipment, especially masks when working to minimize harmful gases. In the air enters the body.Keywords: Health problems, society, piyungan landfill